The Impact of Financial Literacy, Financial Behavior, Income, and Financial Risk Tolerance in the Case of Surabaya University Students’ Investment Decision - Fernando Fernando; David Anderson Pribadi (iBuss Management, 2022)
Investing is an act of putting extra funds or money in an asset to get future benefits in the form of capital gains/dividends/interest. Someone could decide whether to put the money in an asset or not. From 2020 to 2021, the total number of Indonesian investors increased by 57% or becoming 6,100,000. The younger investors within the age of 18-25 or can be categorized as university student age, hold 36% of the total investors of all ages. Surabaya is also one city that leads East Java in terms of the number of investors contributing 98,142 out of 360,414 investors in East Java. The researchers put financial literacy, financial behavior, income, and financial risk tolerance as the independent variable. The dependent variable of this research is investment decision. To do this research, an online survey was done, and the researchers were able to attain 224 respondents. The data is analyzed by using Binary Logistic regression through IBM SPSS statistics. After the data is processed, the researchers found out that financial literacy, financial behavior, income, and financial risk tolerance impact Surabaya university students’ investment decision.Keywords: Investment decisions, Financial literacy, Financial behavior, Income, Financial risk tolerance